INDICATIONS FOR THE DETECTION OF BLADDER CANCER IN THE REPUBLIC OF UZBEKISTAN IN STAGES I-II AND III - IV IN 2017-2021 - Tuychiev A. P (Scholar Express Journals, 2023)
According to new data, in 2020, 573,278 people worldwide were diagnosed with bladder cancer, making bladder cancer the 10th most diagnosed in the world. According to new data, there were 440-864 new cases of bladder cancer in men worldwide, accounting for 4.4 percent of total new cases
Keywords: cancer; worldwide; bladder; new